Barriers, Costs, and Attitudes Toward Pediatric Cataract Surgery at Two Large Facilities in China and India. (2nd January 2019) - Wang, Jun; Jin, Ling; Lu, Qing; Borah, Rishi Raj; Ali, Rahul; Li, Junhong; Chakraborti, Chandni; Kumar, Manish; Pan, Jessica; Gilbert, Clare; Congdon, Nathan
ABSTRACT: Purpose : To better understand barriers of costs and attitudes toward pediatric cataract surgery in China and India. Methods : From January 2014 to June 2015, families of children ≤ 10 years old about to undergo or having completed surgery for bilateral, non-traumatic cataract at two tertiary centers in China and India completed questionnaires regarding their demographic characteristics, financial status, living environment, health seeking behaviors, and medical burden. Results : In China, 38 children (23 boys [60.5%], mean age 3.11 ± 2.88 years) were un-operated, and 44 (26 boys [59.1%], mean age 5.09 +/– 2.17 years) had undergone surgery, while in India there were 60 (44 boys [73.3%], mean age 4.61 +/– 3.32 years) and 39 (29 boys [74.4%], mean age 6.45 +/– 2.74 years) children respectively, 181 in total. Chinese children were younger at presentation (p ≤ 0.03 for both operated and un-operated) and also when cataract was detected (median [inter quartile range] 10 [3–34] versus 24 [6–60] months [p = 0.06] for un-operated, 5 [2–12] versus 36 [8–72] months [p < 0.001] for operated). Maternal education levels were lower in India (48.3% and 51.3% with elementary education only among un-operated [p = 0.11] and operated [p = 0.006] families in India versus 27.0% and 20.5% in China), as were rates of consulting medical practitioners for illness (44.7% and 36.4% for un-operated [p < 0.001] and operated [p = 0.001] in China versus 10% and 5.13% in India). Conclusions : Socioeconomic challenges to securing cataract surgery may be greater, and delays in obtaining surgery longer, in India compared to China, if these facilities are representative.